2013
DOI: 10.1002/bdra.23209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating eight newly identified susceptibility loci for nonsyndromic cleft lip with or without cleft palate in a Mesoamerican population

Abstract: Background: Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is among the most frequently occurring congenital malformations worldwide. The number of genetic loci identified as being involved in NSCL/P etiology was recently increased by a large genome-wide meta-analysis of European and Asian samples. This meta-analysis confirmed all six previously recognized genetic susceptibility loci and identified six novel ones. Methods: To investigate which of these 12 loci contribute to NSCL/P risk in an inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
(27 reference statements)
1
18
1
Order By: Relevance
“…Although a mechanism for how these interactions contribute to specific cleft types is currently unknown, these results build upon our knowledge of the complex and heterogeneous genetic architecture of OFCs, and could inform future biological experiments. Substantial evidence now exists that the FOXE1 locus is associated with all subtypes of OFCs (Leslie et al, 2017; Ludwig et al, 2014; Marazita et al, 2009; Moreno et al, 2009). As the lip develops prior to the palate, it is tempting to speculate that the function of the novel genetic element in 16q21 is to promote proper palatogenesis; however, the genetic architecture of OFCs and, in general, craniofacial development is very complex and interactions with other genetic, environmental, or stochastic factors are likely to contribute overall risk to OFC and the specific type of cleft that results in the child.…”
Section: Discussionmentioning
confidence: 99%
“…Although a mechanism for how these interactions contribute to specific cleft types is currently unknown, these results build upon our knowledge of the complex and heterogeneous genetic architecture of OFCs, and could inform future biological experiments. Substantial evidence now exists that the FOXE1 locus is associated with all subtypes of OFCs (Leslie et al, 2017; Ludwig et al, 2014; Marazita et al, 2009; Moreno et al, 2009). As the lip develops prior to the palate, it is tempting to speculate that the function of the novel genetic element in 16q21 is to promote proper palatogenesis; however, the genetic architecture of OFCs and, in general, craniofacial development is very complex and interactions with other genetic, environmental, or stochastic factors are likely to contribute overall risk to OFC and the specific type of cleft that results in the child.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the broader implications of risk for orofacial clefts in diverse ethnic/racial populations is likely to provide more insight into the underlying etiology. To date, genome‐wide studies have successfully identified several risk loci for orofacial clefts [Birnbaum et al, ; Grant et al, ; Beaty et al, ; Mangold et al, ; Ludwig et al, ; Ludwig et al, ], but are limited in generalizability to other populations. Using data on families from three countries, the DRC, Vietnam, and the Philippines, we conducted a genome‐wide analysis of exonic SNPs as well as custom fine mapping of known cleft susceptibility regions, and replicated the following chromosomal regions as susceptibility regions: 1q32.2, 10q25.3, and 17q22.…”
Section: Discussionmentioning
confidence: 99%
“…A genome‐wide meta‐analysis of 1,461 European/Asian trios and 399 European cases and 1,318 controls identified an additional six regions [Ludwig et al, ]. Eight regions were confirmed in a subsequent study of 153 Mesoamerican cases and 337 controls [Ludwig et al, ]. Given the magnitude of the risk (OR = 1.5–4.0) and the relatively small sample size in particular in diverse populations, it is highly plausible that additional loci are yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Figure , the LD patterns were different between European and Asian trios. Previous studies also demonstrated that the association between genetic susceptibility loci and NSCL/P may be population related (Beaty et al., ; Ludwig et al., , ). For this reason, further validation of our finding and exploration of potential biological function of the putative susceptibility to G×G interactions in different populations are required to interpret the complexity of genetic contribution to NSCL/P etiology (Martinelli et al., ; Poswillo, ).…”
Section: Discussionmentioning
confidence: 89%